2022
DOI: 10.22146/aij.v8i2.76725
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Straw using Combination of Unused Rice and Rice Bran

Abstract: Plastics waste has been recently recognized as one of the most critical environmental issues. The most plastic is not recycleable and it takes 300-500 years to degraded perfectly. Plastics straw also contribute these negative impacts, so develop the biodegradable straw can be one of the solution. Natural ingredients that contain carbohydrates can be used as biodegradable straw materials are unused rice and rice bran, with glycerin from used cooking oil. This study aims to find out the effects of composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…These results are important because the flexibility of the material affects its suitability as a drinking straw, with a more flexible material being more desirable to prevent breakage during use. The obtained value of EAB is higher as compared to bioplastic straws with 6-9 [40], biodegradable drinking straws from a combination of rice bran and unused rice with 0.43-1.71% [41]. A higher EAB indicates greater flexibility and durability, which are desirable properties for a drinking straw.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…These results are important because the flexibility of the material affects its suitability as a drinking straw, with a more flexible material being more desirable to prevent breakage during use. The obtained value of EAB is higher as compared to bioplastic straws with 6-9 [40], biodegradable drinking straws from a combination of rice bran and unused rice with 0.43-1.71% [41]. A higher EAB indicates greater flexibility and durability, which are desirable properties for a drinking straw.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…Compared with another study, Putri & Falah (2020) have developed biodegradable straw using combination of unused rice and rice bran. The study showed that biodegradable straw that made by unused rice and rice brand has a higher value in water uptake and biodegradation value, but lower in elongation value compared with biodegradable straw from ambon banana peel waste.…”
Section: Water Uptakementioning
confidence: 99%